DETERMINANTS OF FIRM VALUE AND ITS IMPACT ON STOCK PRICES (STUDY IN CONSUMER GOOD PUBLIC COMPANIES IN IDX 2014-2018) - M. Noor Salim; Zaky Firdaus (Dinasti Publisher, 2020)
The purpose of this study is to examine and analyze the effect of profitability proxied by Return on Assets (ROA), capital structure proxied by Debt to Asset Ratio (DAR), and Pruchasing Manager Index Manufacture (PMI) on the value of a company that is proxied by Price to Booked Value (PBV) and its impact on Stock Price. The object of this research is the consumer goods companies listed on the Indonesia Stock Exchange period 2014 - 2018. The sample collection technique used was purposive sampling, where 14 companies met the criteria. The analysis used is panel data regression analysis. The results of this study indicate individually ROA and DAR significantly influence PBV while PMI has no effect. ROA, DAR and PMI have no significant effect on stock prices. Then through PBV as an intervening variable, ROA and DAR significantly influence stock prices, while PMI has no effect. Simultaneously ROA, DAR and PMI have a significant effect on stock prices through PBV as an intervening variable.